2019
DOI: 10.1515/sjpain-2019-0055
|View full text |Cite
|
Sign up to set email alerts
|

Experimental shoulder pain models do not validly replicate the clinical experience of shoulder pain

Abstract: Background and aimsPeople with shoulder pain often present with abnormal shoulder muscle function. It is not known whether shoulder pain causes or is the result of muscle dysfunction. If pain leads to muscle dysfunction, therapeutic interventions that produce shoulder pain may be contraindicated. Experimentally induced nociception can be used to investigate a causal relationship between shoulder pain and muscle dysfunction. However, the validity of current experimental shoulder pain protocols has not been esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In a repeated measures design, participants took part in two experimental sessions, separated by at least 3 days (median [1st quartile, 3rd quartile]: 9 [7,16] days). Participants were asked to avoid any strenuous exercise before each session.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a repeated measures design, participants took part in two experimental sessions, separated by at least 3 days (median [1st quartile, 3rd quartile]: 9 [7,16] days). Participants were asked to avoid any strenuous exercise before each session.…”
Section: Methodsmentioning
confidence: 99%
“…However, spontaneous and movement‐induced pain are defined as different features of musculoskeletal pain, 13 and therefore tonic pain models may not accurately replicate the motor adaptations induced by movement‐evoked pain, which is commonly observed in pathologies such as patellofemoral pain 7 and patellar tendinopathy 14 . In fact, it has been reported that pain induced with injection of hypertonic saline solution is often alleviated by movement or muscle contraction 12,15,16 . When investigating motor adaptations to pain, this paradoxical association between movement and pain may lead to a perception of movement as less threatening than what occurs when the movement elicits pain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation